POLA KOMUNIKASI KELUARGA DALAM MENCEGAH NOMOPHOBIA PADA ANAK USIA SEKOLAH MENENGAH PERTAMA DI KECAMATAN PANGEAN - ALFI, MHD. ALFI; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The importance of communication patterns that exist between parents and children in shaping children's character and maintaining family harmony. This study aims to find out how permissive communication patterns, authoritarian communication patterns and authoritative communication patterns between parents and children. This research is a descriptive qualitative research using data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman models. The research results show that permassive communication patterns can make children experience nomophobia, it can be seen that parents are too liberating and have low control over children in using mobile phones. Even though parents still give warnings to children and occasionally supervise, children still play their cellphones more often than interact with their parents. So that the communication that exists between parents and children is less effective because the communication that is established is only one-way communication. whereas in the authoritarian communication pattern parents always supervise and limit the time they play gadgets and use gadgets only for study purposes. and authoritative is characterized by an open attitude between parents and children. They make some kind of rules that are mutually agreed upon so that children will listen and obey what their parents say. Keywords: Family Communication Patterns, Parent and Child Communication, Nomophobia